“Menyusui asi-q” android application for relax and smooth breastfeeding - Kharisma Virgian; Desy Setiawati Setiawati (Institute of Computer Science (IOCS), 2023)
Breastfeeding is an instinct of a mother, however, it must be supported by internal factors and good external. The success of the breastfeeding process can be supported by knowledge, good social support, calmness, and comfort of the mother when breastfeeding. One form of support as an educational and relaxation medium developed for breastfeeding mothers is the android-based